1989
DOI: 10.1093/jnci/81.16.1241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Quality on Development of Aflatoxin B1 -Induced Hepatic Preneoplastic Lesions

Abstract: The effect of the quality of dietary protein on the post-initiation development of aflatoxin B1-initiated putatively preneoplastic foci in Fischer 344 rat liver was compared with the effect of the quantity of dietary protein. Feeding wheat gluten, a low-quality protein, during the postinitiation period (between the end of aflatoxin B1 dosing and the death of the rats) inhibited the development of gamma-glutamyltransferase-positive foci when compared with that in animals fed high-quality protein (casein) diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Previous studies have shown considerable variability in AFB-induced foci response among identically treated rats [8,14,26,27]. The source of this variability is unknown but may be compensated for by a large number of animals per group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown considerable variability in AFB-induced foci response among identically treated rats [8,14,26,27]. The source of this variability is unknown but may be compensated for by a large number of animals per group.…”
Section: Discussionmentioning
confidence: 99%
“…(14') Finally, decreasing the quality as well as the quantity of dietary protein after aflatoxin exposure inhibits the development of preneoplastic lesions. (148) Choline deficiency in the diet increases the incidence of AFB,-induced tumors in DNA adduct levels followed different kinetics in animals maintained on this diet for 3 weeks prior to exposure and during multiple exposures to AFB, (five daily exposures per week for 2 weeks) compared with animals maintained on the control diet. (150) In particular, AFB,-DNA binding in animals fed the choline-deficient diet was maximal in the middle of each exposure week, compared with no significant peak in adduct levels in control animals.…”
Section: Effect Of Diet On the Balance Between Activation And Detoxifmentioning
confidence: 96%
“…Follow-up studies (e.g., Appleton and Campbell 1982;Dunaif and Campbell 1987) addressed cancer promotion after initiation, showing dramatically increased precancerous deformities in response to a given carcinogen dose under high animal protein diets. To unambiguously implicate animal protein in the observed enhanced cancer promotion, Schulsinger et al (1989) compared induced carcinogenesis under high protein diets of animal and plant origins. Cancer promotion was significantly enhanced under animal-protein-rich diet.…”
Section: Are Plant-based Diets Safe?mentioning
confidence: 99%